Flow approach - finite element model for stamping processes versus experiment - Sosnowski, Włodzimierz (Computer Assisted Methods in Engineering and Science; Vol 1 No 1-2 (1994), 2023)
In this paper, information on a sheet metal formig simulation program based on flow approach is provided ud comparisons between numerical and experimental raults are presented. Elastic spring-back effects and residual stresses are predicted by means of a large-strain elasto-viscoplastic finite element model recently proposed. for this class of problems involving large deformations and changes in geometry. A wide experimental program performed in a sheet stamping factory is shortly described. Tests included the deep drawing of circular and rectangular blanks with cylindrical and prismatic tools, respectively. Different die and punch roundings, lubrication conditions and blank holder forces have been considered. Different examples of application to 20 and 3D sheet stamping problem. are presented and compared with available experimental results.